2020
DOI: 10.1016/j.aquaculture.2020.735511
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the effect of fish meal substitution with three different insect meals on growth, body composition and metabolism of European sea bass (Dicentrarchus labrax L.)

Abstract: A comparative study on the effect of fish meal substitution with three different insect meals on growth, body composition and metabolism of European sea bass (Dicentrarchus labrax L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 82 publications
3
62
0
Order By: Relevance
“…The feeding trial of Basto, et al [ 60 ] indicated the potential ability of defatted TM larvae to substitute up to 80% of FM in D. labrax diets. A recent study by Mastoraki, et al [ 23 ] suggested that 30% of FM can be effectively substituted with whole TM larvae, with no harmful impacts on the fish growth performance. Interestingly, Reyes, et al [ 61 ] reported that substitution of less than 50% of FM in sea bass diets with TM larvae did not influence on growth indices or proximate analysis of the fillets.…”
Section: Dietary Inclusion T Molitor With Possmentioning
confidence: 99%
See 4 more Smart Citations
“…The feeding trial of Basto, et al [ 60 ] indicated the potential ability of defatted TM larvae to substitute up to 80% of FM in D. labrax diets. A recent study by Mastoraki, et al [ 23 ] suggested that 30% of FM can be effectively substituted with whole TM larvae, with no harmful impacts on the fish growth performance. Interestingly, Reyes, et al [ 61 ] reported that substitution of less than 50% of FM in sea bass diets with TM larvae did not influence on growth indices or proximate analysis of the fillets.…”
Section: Dietary Inclusion T Molitor With Possmentioning
confidence: 99%
“…However, Reyes, et al [ 61 ] recorded no significant differences in the FCR and PER in D. labrax fed for 49 days a diet with 50% of FM replaced with TM larvae compared with the FM-based group. Mastoraki, et al [ 23 ] reported no significant differences in the SGR, FI, viscerosomatic index (VSI), hepatosomatic index (HSI), and relative gut length (RGL), alongside a slight increase in the FCR, in D. labrax fed diets with 30% of FM replaced with whole TM larvae for 84 days compared with the FM group.…”
Section: Effects Of Dietary Supplementation With T Molimentioning
confidence: 99%
See 3 more Smart Citations